Planning start-up: digital educational game solutions provider - Paschalis, Antreas; Ibironke, Fakinkunmi; Essa, Lubna; Alsatrawi, Ali Jawad (2015)
Game-based learning is a growing field that provides education with a new perspective of teaching through games. Game based learning is still considered an emerging field due to problems that have been identified in its real applications in official education in classes. The research conducted shows a very attractive market ahead for game based learning around the world. However the businesses success in this domain lie in providing value proposition that addresses the real barriers faced today. Prime Ace is a company that has been conceptualized to be starting up via an equal partnership among the four students from the University of Nottingham, Computer Science and Entrepreneurship course who are doing this dissertation. Prime Ace is a digital educational game solutions provider that is ambitious to be a leader of its focused market in providing education to children through games not only at home but also in class. Its products and services will span to the teachers and parents to help them through their mission of educating children in its innovative way. Based on the theory studied and practical opportunity, Prime Ace aims to target the Middle Eastern game based learning market. It has taken a focused marketing approach in targeting the attractive demographic group of kindergarten levels up to primary grade level two (prek-2). The company has drawn a detailed 5-year operational and financial plan. Based upon them, the company is seeking a seed investment of $150,000 (USD) at this stage in order to move on to its next stage of moving to Dubai. Prime Ace has so far conducted its first project and digitized and implemented a serious board game which targets its own market. The game aims to teach students how to manipulate DNA in a completely safe and low-cost environment rather than necessarily performing these tasks in actual labs to learn. Prime Ace have had a fair portion of experience in working with a real client, actually developing game and understanding specific learning objectives. The team have gained valuable experience on how to work together with a real client to solve project related problems. The problems faced include software development problems such as unfamiliarity with the development software as well as project management problems such as unclear and changing requirements. The team has learnt to work on solving these problems by following industry practices on software development methodology, using appropriate tools and processes, linking theoretical research of Human-Computer Interaction and artificial intelligence. After multi-level and stage-by-stage testing which involves actual users, the product has shown potential its effectiveness for learning. The project’s dissertation requirements were exceeded, producing more than a demo. The project’s client expectations were also exceeded and he was able to use the product for his purpose of pitching for investments. Last but not least, the project’s team goals were met as it has proven them as an effective team that is hopefully worthy to invest in.